Hetero-Integration of β-Ga2O3 and Diamond Substrates by Hydrophilic Bonding Technique. (8th September 2020) - Matsumae, Takashi; Kurashima, Yuichi; Takagi, Hideki; Umezawa, Hitoshi; Tanaka, Koji; Ito, Toshimitsu; Watanabe, Hideyuki; Higurashi, Eiji
Abstract : A β-Ga2 O3 film was directly bonded on a diamond substrate at 250ºC under atmospheric conditions. Before bonding, the β-Ga2 O3 surface was activated by oxygen plasma irradiation, while the diamond surface was cleaned with H2 SO4 /H2 O2 and NH3 /H2 O2 mixtures. The β-Ga2 O3 anddiamond surfaces adhered to one another under atmospheric conditions. By annealing the contacted specimen at 250ºC, they formed atomic bonds without voids, cracks, or severe crystallinity damages. It is believed that the direct bonding of β-Ga2 O3 and diamond can facilitate the ultra-wide bandgap power electronics.